Meaning in life, meaning-making and posttraumatic growth in cancer patients: Systematic review and meta-analysis - Almeida, Margarida; Ramos, Catarina; Maciel, Laura; Basto-Pereira, Miguel; Leal, Isabel (Frontiers in Psychology, 2022)
The purpose of this systematic review and meta-analysis is to assess the association between meaning in life (MiL), meaning-making and posttraumatic growth (PTG) in the context of cancer. A systematic search was conducted in eighteen electronic databases. The screening and selection process followed the PRISMA guidelines. For the purpose of the meta-analysis, the correlation coefficients between meaning in life and posttraumatic growth were extracted from the included studies. The effect size (r) was calculated using the restricted maximum-likelihood estimator, a random-effects model. Heterogeneity was assessed through the Q statistic, I2 index and forest plot, while publication bias was analyzed with the use of the funnel plot and Egger’s test. 889 records were considered according to the inclusion criteria. A total of nine articles, published between 2006 and 2021, were included in the systematic review. More than half were published in the last five years. The sample was mostly diagnosed with breast cancer. The meta-analysis included five articles (N = 844) and the results indicate a significant moderate correlation between meaning in life and posttraumatic growth (r = 0.43, 95% IC [0.36, 0.50]). In conclusion, there is a clear association between meaning in life and posttraumatic growth in cancer patients. Future research should explore this relationship further, in order to better assist and guide meaning centered interventions that can potentiate a positive adjustment and possibly growth from the cancer experience.